Urgency of Realizing Bystander Concept In Preventing Crime Victims - Rani Hendriana; Agus Raharjo; Nabila Puspakesuma; Lintang Ario Pambudi (Universitas Negeri Semarang, 2025)
Bystander Intervention has a strategic role in preventing crime, although psychologically, most people are more apathetic and morally do not take part in social responsibility. This research aims to explore Bystander Intervention as an ideal concept for preventing victims. As it has developed in other countries, it is important to realize Bystander Intervention in Indonesia through local wisdom values and criminal law norms. This research adopts a normative juridical approach, incorporating comparative, conceptual, and statutory approaches. It was revealed that Bystander Intervention is an ideal concept for preventing crime because it offers two forms of direct and indirect intervention. In some countries, this concept has been successfully developed with a programmatic approach through measurable training and Bystander Intervention education curriculum to encourage students and adults to prevent victims. Indonesia does not recognize the concept of Bystander. However, Articles 532 of the Criminal Code and 432 of the Criminal Code 2023 provide opportunities, and there is harmony between the concept of Bystander Intervention and local wisdom values involving the principles of kinship, cooperation, and helping. These opportunities need to be realized by encouraging the effectiveness of criminal sanctions and re-igniting local wisdom values while integrating them with international practices so that realization does not only rely on criminal sanctions but also programmatic approaches.